Ministry Of Tourism and Antiquities Decree No. 304 Of the Year 2021 Issued On 29/11/2021 = وزارة السياحة والآثار قرار رقم 304 لسنة 2021 صادر تاريخ 29/11/2021 - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic